(NdNEWNIKI (B1905-1954 /s (N~ASTX (B8s - (NpRI[WIN(B, (NmIHAILs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1986)
(Nw TOM WO[LI DNEWNIKI m(B.(Nm(B. (NpRI[WINA(B, (NOHWATYWA@]IE POLWEKA VIZNI I TWOR^ESTWA PISATELQ(B, (NS (B1905 (NPO (B1954 (NGOD(B.s
rus
Keywords: (NdNEWNIKIs